Corporate Social Responsibility Disclosure and Firm Value from Accounting Perspective - Rahimi, Rezvan (Business, Marketing, and Finance Open, 2025)
This study aimed to explore the relationship between corporate social responsibility (CSR) disclosure and firm value from an accounting perspective. A qualitative research design was employed, utilizing semi-structured interviews with 24 accounting professionals, corporate executives, and financial analysts from Tehran. Purposive sampling ensured participants possessed relevant expertise, and data collection continued until theoretical saturation. Nvivo software was used for thematic analysis, involving open, axial, and selective coding to identify key themes related to CSR disclosure and firm value. The study revealed that CSR disclosure positively influences firm value by enhancing financial performance through improved profitability, revenue stability, and operational efficiency. It increases investor trust by reducing risk perception and fostering long-term investment. CSR initiatives contribute to market competitiveness by strengthening brand reputation and customer loyalty, while also ensuring regulatory compliance by reducing legal risks and fostering positive relationships with policymakers. Challenges such as high implementation costs, lack of standardized metrics, and internal resistance were also identified, along with the critical role of strong corporate governance in ensuring effective CSR disclosure. CSR disclosure is a strategic tool that enhances firm value through financial performance, investor trust, market competitiveness, and regulatory compliance. Despite the challenges associated with CSR implementation, firms that adopt comprehensive CSR disclosure practices benefit from improved financial outcomes and competitive positioning. Strong governance structures are essential for effective CSR reporting, ensuring transparency and accountability in corporate practices.